THE EFFECTS OF RINGLEADER DISCRIMINATION ON CARTEL STABILITY AND DETERRENCE – EXPERIMENTAL INSIGHTS - Hesch, Michael (Journal of Advanced Research in Law and Economics; Vol 3 No 1(5) (2012): Volume III, Issue 1(5), Summer 2012, 2017)
Cartel ringleaders make significant contributions to enabling illegal collusive agreements to function. According to US legislation, ringleaders are excluded from corporate leniency programs. Since 2002, under EU regulations, ringleaders may qualify for a reduction of fines. To date, both antitrust laws treat cartel ringleaders differently. We analyze the impact of this difference in a cartel experiment. Given a low probability of detection through an authority, we find that excluding ringleaders from leniency facilitates cartel formation, stabilizes collusion and leads to significantly higher market prices. The opposite holds for a high probability of detection. Here, the results are in line with the situation when every player can apply for leniency.